1976
DOI: 10.1161/01.cir.53.3.464
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve prolapse in one hundred presumably healthy young females.

Abstract: Clinical, electrocardiographic, phonocardiographic, and echocardiographic examinations were performed in 100 presumably healthy young females. Treadmill testing and ambulatory electrocardiographic monitoring were performed in a selected group of these subjects. Phonocardiograms, recorded with the subjects supine at rest, after inhalation of amyl nitrite, and in the upright position, revealed a 17% incidence of nonejection clicks and/or late or mid- to late systolic murmurs (PHONO-MSCLSM). Echocardiographic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0
4

Year Published

1977
1977
1985
1985

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(89 citation statements)
references
References 35 publications
4
81
0
4
Order By: Relevance
“…The prevalence figures reported include 1.4% of black South African school children,2 5% in routine autopsies of patients over 40 years of age,6' 7 and 6-10% of presumably normal young women studied by echocardiography. [8][9][10] In this study we assessed the prevalence of mitral valve prolapse in a group of young healthy adult males.…”
mentioning
confidence: 99%
“…The prevalence figures reported include 1.4% of black South African school children,2 5% in routine autopsies of patients over 40 years of age,6' 7 and 6-10% of presumably normal young women studied by echocardiography. [8][9][10] In this study we assessed the prevalence of mitral valve prolapse in a group of young healthy adult males.…”
mentioning
confidence: 99%
“…1 ' 2 The prolapse may be idiopathic 3 or associated with a wide variety of underlying conditions. 312 Some authors have observed abnormal patterns of left ventricular contraction and suggested the involvement of a myocardial component in this syndrome.…”
mentioning
confidence: 99%
“…In fact, mitral valve prolapse has been suggested to be a form of developmental connective tissue disorder (Salomon et al, 1975;Udoshi et al, 1979). This crosssectional survey demonstrated a relatively low prevalence of mitral valve prolapse compared with previous observations (Darsee et al, 1978;Markiewicz et al, 1976;Sbarbaro et al, 1979). Variance in somatic features among ethnic groups may explain this difference in its prevalence.…”
Section: Discussionmentioning
confidence: 61%
“…Although significant clinical *Presented in part at the IX World Congress of Cardiology in Moscow, USSR, June 1982. manifestations may be present in this syndrome, a high incidence of asymptomatic cases have been reported (Brown et al, 1975;Darsee et al, 1978;Markiewicz et al, 1976;Sbarbaro et al, 1979).…”
Section: Introductionmentioning
confidence: 99%